Regarding the parent bodies in the Meteor Data Center - Ďurišová, Silvia; Hajduková, Mária; Rudawska, Regina; Jopek, Tadeusz J.; Neslušan, Luboš (The International Meteor Organization, 2024)
Currently, the only known database containing both meteor shower parameters and the parent bodies associated with them is the IAU Meteor Data Center (MDC) Shower database (SD). But only about 16% out of all the listed showers have a parent body linked to them. As part of the ongoing modification of the SD, we aim to identify as many scientific sources suggesting shower parent bodies as feasible and enhance the database by including this information, along with method of investigation and the corresponding references.